Kompleksitas lanskap pertanian dan pengaruhnya terhadap keanekaragaman Hymenoptera parasitika - Sumeinika Fitria Lizmah; Damayanti Buchori; Pudjianto Pudjianto; Akhmad Rizali (Jurnal Entomologi Indonesia, 2018)
The complexity of agricultural landscape can affect biodiversity in agroecosystem. Complex landscape tend to have higher diversity and composition of spesies than simple landscape. The aim of this research was to study the diversity and species composition of parasitic Hymenoptera under different complexity of agricultural landscape. Field research was conducted at four cucumber fields in Bogor District with two fields were located in complex agricultural landscape as well as simple agricultural landscape. In each cucumber field, plot with size 25 m x 50 m was provided for sampling of parasitic Hymenoptera which was conducted using yellow pan trap, malaise trap and host collection within transect. In total, 233 species of parasitic Hymenoptera were found from four cucumber fields during two planting seasons. The result showed that the diversity and species composition of the Hymenoptera parasitic did not differ between simple and complex agricultural landscapes. It indicates that the diversity and species composition of parasitic Hymenoptera on cucumber plantation in Bogor was not affected by landscape complexity.